Listening attitudes, principles, and skills - Brownell, Judi 1949- (Routledge, Taylor & Francis Group, 2024)
This fully updated seventh edition takes an experiential approach to listening instruction, providing extensive applied examples and cases within the context of the HURIER listening model. This textbook encourages students to view listening as a process involving six interrelated components-hearing, understanding, remembering, interpreting, evaluating, and responding-which are developed along the parallel dimensions of theory and skill building. This book considers various contexts of listening in family relationships, education, healthcare, and the workplace, as well as digital media. It discusses the challenges of ethical listening, the requirements of listening across generations and the role mindfulness plays in listening effectiveness. This new edition includes additional and updated cases, exercises, and questions that examine evolving technologies, expanding social boundaries, and global communication challenges. It explores new topics such as the opioid crisis, fake news, artificial intelligence, and teenage mental health. A new Integrative Listening model addresses social responsibility and shows students how to use respectful and inclusive dialogue to create strong listening environments. Listening serves as a core textbook for courses in listening, communication studies, communication skills, interpersonal communication, management, human resources and education"--